2009
DOI: 10.5539/jas.v1n2p94
|View full text |Cite
|
Sign up to set email alerts
|

Study on Extraction and Purification Process of Capsicum Red Pigment

Abstract: Capsicum red pigment extracted from the dry pepper is a kind of high-quality natural dye which has anticancer and cosmetic properties. First, Qiu North spicy was selected as the experimental objects by comparising the peel meal rate and relative amount of pigment of Fructus capsici, Qian chilli 2, and Qiu North spicy. Then, before extracting paprika dye, sodium hydroxide was used to eliminate the piquancy. Capsicum red pigment was extracted in Soxhlet extractor with 95% ethanol. The elution condition of column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It has also been shown that pretreatment of the flour with enzymes those break cell wall enhanced the recovery of carotenoids by 11 %. Pretreatment of capsicum powder with 10-30 % sodium hydroxide and subsequent extraction with ethanol has been reported to yield pungent free red pepper colorant (Chen and Wu 2009).…”
Section: Extraction and Pretreatment Of Samplesmentioning
confidence: 99%
“…It has also been shown that pretreatment of the flour with enzymes those break cell wall enhanced the recovery of carotenoids by 11 %. Pretreatment of capsicum powder with 10-30 % sodium hydroxide and subsequent extraction with ethanol has been reported to yield pungent free red pepper colorant (Chen and Wu 2009).…”
Section: Extraction and Pretreatment Of Samplesmentioning
confidence: 99%
“…Curcumin, blue and purple anthocyanin and carotene pigments were extracted from turmeric, blue pea flower, purple cabbage and dried red chillies, respectively. Dried red chillies were subjected to digestion using sodium hydroxide to remove piquancy prior to pigment extraction (Chen and Wu 2009). All the extracted pigments were concentrated using rotary evaporator.…”
Section: Methodsmentioning
confidence: 99%
“…In fact heat or temperature renders the cell walls to get more permeable, decreases the viscosity of solvent, thus temperature facilitates its passage through solid substrate mass (Tan et al, 2011). Higher temperature turned to damage pigment by loss of protection from membrane, very quickly the colourant self oxidises (Chen and Wu, 2009) [2] . Figure 1c and 1e indicates the effect of material to liquor ratio MLR (C) and extraction temperature (B) on dye yield.…”
Section: Plot Response Surface Design -Interaction Effect Of Factorsmentioning
confidence: 99%